Myth or reality? Unveiling the effectiveness of hierarchical CEO succession on firm performance and cash holdings - Sarfraz, Muddassar; He, Bin; Shah, Syed Ghulam Meran; Fareed, Zeeshan (Journal of Business Economics and Management, 2021)
The objective of the study is to contemplate the effectiveness of hierarchical CEO succession and hierarchical CEO succession intensity on SOEs & Non-SOEs performance separately.  Meanwhile, the impact of hierarchical CEO succession on cash holdings has also been analysed. The authenticated data has been accumulated from CSMAR for the years 2012-2016 contemplating the listed companies (SOE and Non-SOEs separately for performance while overall companies for cash holdings) on Shenzhen and Shanghai stock exchanges. Through categorization of hierarchical CEO succession, it has been signified that middle-level hierarchical CEO succession elevates the SOEs performance. In contrast, middle and high-level hierarchical CEO succession mitigate the cash holdings. Conclusively, earning management as a moderator has been analysed while deducing that hierarchical CEO succession reduces cash holdings despite firms involving earning management activity which is ultimately beneficial for firms’ growth. The empirical results are robust to alternate technique 2SLS instrumental regression that controls for endogeneity.